Parâmetros genéticos para integridade óssea do fêmur e estudo da associação dos genes runx2 e tnfs11 em frangos de corte - Grupioni, Natalia Vinhal [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
In the broiler breeding programs, the broilers are selected primarily for performance and carcass traits, resulting in changes in the size, shape and function of organs which implies important physiological changes during the development of the broilers. Intense selection of broilers resulted in locomotors problems, decreased bone strength of animals and increased mortality. Thus, molecular screening techniques began to be used in order to identify candidate genes to assist in the selection of related traits to bone disorders. The objective of this study was estimate genetic parameters for traits related to femoral integrity bone and weight at 42 days and association study of RUNX2 (Runt-related transcription factor 2) and TNFSF11 (Tumor necrosis factor (ligand) superfamily, member 11) genes with economical traits in broilers in order to provide support for the broiler breeding program and direct the selection process to reduce problems related to bone disorders. Estimates of genetic parameters were obtained for traits associated with the femur bone integrity and weight at 42 days of age by the restricted maximum likelihood method using multi-trait animal model with the fixed group effect (sex and incubation), and the random effects and additives residuals. The investigation of polymorphisms in association RUNX2 genes and TNFSF11 and the association study of polymorphisms found and their respective SNPs (Nucleotide single polymorphism) of RUNX2 genes (SNP g.57.397A>G) and TNFSF11 (SNP g.14.614A> g) with the performance, carcass composition, parts and femoral bone integrity in order to evaluate the effects of these polymorphisms about this group of traits to maximum likelihood method. We used the TT reference population database with about 1,500 broilers belonging to Embrapa Swine and Poultry Breeding Program in Concordia/SC, Brazil. Heritability coefficients estimated for weight at 42 days of age (W42) and the related traits to ...

Em programas de melhoramento de frangos de corte, as aves são selecionadas principalmente para características de desempenho e carcaça, acarretando em mudanças no tamanho, forma e função dos órgãos, o que implica em alterações fisiológicas importantes durante o desenvolvimento das aves. A seleção intensa dos frangos de corte resultou em problemas locomotores, diminuição da resistência óssea dos animais e aumento da mortalidade. Com isso, técnicas de biologia molecular podem ser utilizadas na seleção assistida por marcadores com o intuito de identificar genes candidatos para auxiliar no processo de seleção de características relacionadas às desordens ósseas. Os objetivos do presente trabalho foram estimar os parâmetros genéticos para características relacionadas à integridade óssea do fêmur e peso aos 42 dias de idade e estudar as associações dos genes RUNX2 (Runt-related transcription factor 2) e TNFSF11 (Tumor necrosis fator (ligand) superfamily, member 11) com características de importância econômica em frangos de corte no intuito de fornecer suporte para o programa de melhoramento genético de aves e direcionar o processo de seleção visando a redução dos problemas relacionadas às desordens ósseas. Estimativas de parâmetros genéticos, fenotípicos e ambientais foram obtidas para características associadas à integridade óssea do fêmur e peso aos 42 dias de idade (P42) pelo método de máxima verossimilhança restrita utilizando modelo animal multicaracterística, com efeito fixo de grupo (sexo e incubação) e os efeitos aleatórios genéticos aditivos e residuais. Análises de associações genéticas entre o SNP g.57.397A>G (RUNX2) e SNP g.14.614A>G (TNFSF11) com características de desempenho, composição de carcaça, órgãos e integridade óssea do fêmur foram realizadas com o propósito de avaliar os efeitos desses polimorfismos sobre esse grupo de características, por ...
Keywords: Frango de corte; Genes; Estimativa de parametro; Femur; Genetica animal; Animal genetics